In silico identification of immunodominant B-cell and T-cell epitopes of non-structural proteins of Usutu Virus. (December 2018) - Satyam, Rohit; Janahi, Essam Mohammed; Bhardwaj, Tulika; Somvanshi, Pallavi; Haque, Shafiul; Najm, Mohammad Zeeshan
Abstract: Usutu Virus (USUV; flavivirus) is a re-emerging pathogen invading the territories of European countries, Asia, and Africa. It is a mosquito-borne zoonotic virus with a bi-directional transmission route from animal to human and vice versa, and causes neurological disorders such as meningoencephalitis in bats, Homo sapiens, birds and horses. Due to limited availability of information about USUV and its deleterious effects on neural cells causing neurologic impairments, it becomes imperative to study this virus in detail to equip ourselves with a solution beforehand. The current study aims to identify immunodominant peptides that could be exploited in future for designing global peptide vaccine for combating the infections caused by USUV. In this study, an immunoinformatics approach was applied to evaluate the immunogenicity of 7 non-structural proteins and determined 64 continuous B-cell epitopes, numerous probable discontinuous B-cell epitopes, 64 MHC Class-I binders, 126 MHC class-II binders and 52 promiscuous binders with a maximum population coverage of 98.55%(MHC Class-I binder ofYP_164815.1 NS4a) and 81.81% (MHC Class-II binders of YP_164812.1 NS2a, YP_164813.1 NS2b, YP_164814.1 NS3, YP_164817.1 NS4b, YP_164818.1 NS5). Further, studies involving experimental validation of these predicted epitopes is warranted to ensure the potential of B-cells and T-cells stimulation for their effective use as vaccine candidates, and as diagnostic agents against USUV. Highlights: The study insights into the underlying antigenicity of Usutu virus infection. Immunogenicity of 7 non-structural proteins of Usutu virus was evaluated in-silico . 64 continuous & many discontinuous B-cell epitopes were predicted. 64 MHC class-I, 126 MHC class-II & 52 promiscuous binders were identified. Population coverage analysis revealed 98.55% coverage of the human population.